2003
DOI: 10.1074/jbc.m210733200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Induction of Cell Death by Selenium-compromised Thioredoxin Reductase 1 but Not by the Fully Active Enzyme Containing Selenocysteine

Abstract: Mammalian thioredoxin reductases are selenoproteins. For native catalytic activity, these enzymes utilize a C-terminal -Gly-Cys-Sec-Gly-COOH sequence (where Sec is selenocysteine) forming a redox active selenenylsulfide/selenolthiol motif. A range of cellular systems depend upon or are regulated by thioredoxin reductase and its major protein substrate thioredoxin, including apoptosis signal-regulating kinase 1, peroxiredoxins, methionine sulfoxide reductase, and several transcription factors. Cytosolic thiored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
130
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(136 citation statements)
references
References 44 publications
(29 reference statements)
5
130
1
Order By: Relevance
“…Hence, without resonance effects of Tyr-116 and therefore a lack of an efficient reductive half-reaction, the result would easily be the observed increased propensity for juglone reduction but diminished activity with Trx as substrate. Similarly, the higher resistance to cisplatin derivatization upon Tyr-116 mutation also becomes understandable, because the selenolate of Sec-498 is the prime target for cisplatin targeting (57,69), whereas the selenenylsulfide is essentially inert to reaction with electrophilic compounds (70). Again, if Tyr-116 mutations would lead to an attenuated reduction of the selenenylsulfide, according to the model put forward here, the observed effects on the kinetics of the Tyr-116 mutations become explicable.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, without resonance effects of Tyr-116 and therefore a lack of an efficient reductive half-reaction, the result would easily be the observed increased propensity for juglone reduction but diminished activity with Trx as substrate. Similarly, the higher resistance to cisplatin derivatization upon Tyr-116 mutation also becomes understandable, because the selenolate of Sec-498 is the prime target for cisplatin targeting (57,69), whereas the selenenylsulfide is essentially inert to reaction with electrophilic compounds (70). Again, if Tyr-116 mutations would lead to an attenuated reduction of the selenenylsulfide, according to the model put forward here, the observed effects on the kinetics of the Tyr-116 mutations become explicable.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it was shown that introduction of the SeCys-deficient inactive TrxR1 into A549 human lung carcinoma cells induces rapid cell death [31]. To determine whether or not the TrxR2DN induction also affects cell death, TrxR2DN-induced and -uninduced cells were treated with TNF-a, etoposide, or UV irradiation and then cytoplasmic DNA fragmentation was examined.…”
Section: Effect Of Trxr2dn Induction On Apoptosismentioning
confidence: 99%
“…Therefore, the SeCys residue can act as a cellular redox sensor sensing H 2 O 2 produced in cells which are exposed to the ROS-inducing factors such as epidermal growth factor [13,30]. Recently, it was shown that incorporation of SeCys residue deficient TrxR1 into human cells rapidly induced cell death [31]. From these observations, it is expected that the selenolate anion of SeCys residue of TrxRs is the primary target of ROS produced by TNF-a and that oxidation of the SeCys residue subsequently accelerates ROS mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…TrxR1, a component of the TrxR1/Trx redox system, is a selenoprotein involved in several biological functions, and is known to have either pro-or anti-apoptotic activities, 3,4 probably by regulating genes with opposing functions. Because TrxR1 is target for anti-cancer drugs, 10 the identification of the genes involved in the different responses is extremely important for therapeutic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…While the selenoprotein has proliferative effects, the truncated form exhibits strong pro-apoptotic activity. 3,4 It has been suggested that the TrxR1/Trx system affects cellular processes by regulating the activity of transcription factors, leading to changes in gene expression. Some examples of this are shown in the modulation of p53, 5 NF-kB, 6 Sp-1, 7 and HIF1-α 8 .…”
Section: Introductionmentioning
confidence: 99%